Stability Assessment of Rydberg Electromagnetically Induced Transparency Locking via Optical Heterodyne Spectroscopy - Yin, Qiuyu; Liang, Yanzhao; Lin, Haitao; Ji, Ning; Vogt, Thibault (Photonics, 2025)
Frequency locking to reference atomic lines using Rydberg electromagnetically induced transparency (EIT) has been recently introduced as an inexpensive and reliable technique for laser frequency stabilization. In this work, we carry out a systematic study of this technique using heterodyne beat spectroscopy. Two different commercial semi-conductor lasers are locked to the same reference frequency using EIT locking, and their relative frequency stability is analyzed and continuously monitored in real time. A substantial improvement in the laser frequency stability is achieved through searching for the optimal proportional–integral settings and EIT probe laser powers. The results show that the cutoff frequency of the beat signal can be lowered to less than 500 kHz. We also compare the frequencies of free running lasers with that of a locked laser and characterize their frequency drifts. This study is important in assessing the use of Rydberg EIT locking in atomic electrometers.